The Austrian School´ s perspective on the Brazilian airport concession - Arantes, Elaine; Piaskowski, Otavio Ferrari (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
The concession of the Guarulhos, Viracopos and Brasilia airports is discussed from the perspective of the Austrian School based on the Austrian Theory of Market Process (KIRZNER, 1997; BARBIERI, 2001) and the Austrian Theory of Economic Intervention (MISES, 2010b). The problem observed is that the state is the granting authority, regulatory body and partner in the concessionaire. The results indicate that the presence of the state prevents the efficiency of entrepreneurial management, the discovery of new knowledge and the stimulation of competition. It is due to the fact that the Brazilian Airport Infrastructure Company (INFRAERO) is present in the management of airports granted and not granted. INFRAERO was negatively impacted as it lost part of its revenue from surplus airports and maintained its responsibility for managing low-income or deficit airports. Ludwig von Mises’s Theory of Interventionism, written in the 1940s, remains contemporary and guides the process of organizational management.